MBD the family book about minimal brain dysfunction - Gardner, Richard A. (New York Jason Aronson, 1973)
An introduction for parents and children to the causes, effects, and misconceptions of minimal brain dysfunction, and the best way of dealing with this disorder.
pt. 1. For parents - pt. 2. For boys and girls
1
Keywords: Minimal brain dysfunction in children; Minimal brain dysfunction in children -- Juvenile literature